Strategi Pengembangan Mobil Listrik dalam Mendukung Sustainable Development Goals di Indonesia - Nuzla Nurfauziah; Asnita Frida B.R. Sebayang (Bandung Conference Series: Economics Studies, 2024)
Abstract. The electric car industry contributes to an economy that considers environmental impacts in addition to the needs of society and supports the challenges of Indonesia's sustainable development goals (SDGs) in improving air quality. Delays in the development and implementation of energy and power generation projects and investment barriers in the electricity and renewable energy sectors, resulting in non-achievement of the renewable energy mix target in Indonesia. This study aims to identify and analyze the development strategy of the electric car industry in Indonesia in order to support the achievement of SDGs 7 relating to clean and affordable energy. This research uses secondary data with a mixed methods approach which is a Pearson correlation test to measure variable correlation and SWOT analysis to formulate strategies. The population that is the focus of this research is data on electric car sales in Indonesia which affects air pollution levels, air quality and affects SDGs 7. The results showed a strong correlation between an increase in the number of electric cars and the air quality index and a decrease in pollution levels and the achievement of SDGs 7. The Indonesian government still has challenges such as inadequate charging infrastructure and high selling prices. The proposed strategies include improving regulatory policies, developing environmentally friendly charging infrastructure, and encouraging cooperation and investment, especially in encouraging domestic elements. Abstrak. Industri mobil listrik berkontribusi pada perekonomian yang memperhatikan dampak lingkungan selain kebutuhan masyarakat serta mendukung tantangan sustainable development goals (SDGs) di Indonesia dalam meningkatkan kualitas udara. Keterlambatan dalam pengembangan dan pelaksanaan proyek energi dan pembangkit listrik dan terdapat hambatan investasi di sektor ketenagalistrikan dan energi terbarukan, sehingga tidak tercapainya target bauran energi terbarukan di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi pengembangan industri mobil listrik di Indonesia dalam rangka mendukung pencapaian SDGs ke 7 yang berkaitan dengan energi bersih dan terjangkau. Penelitian ini menggunakan data sekunder dengan pendekatan mixed methods yang merupakan uji korelasi pearson untuk mengukur korelasi variabel dan analisis SWOT untuk merumuskan strategi. Populasi yang menjadi fokus pada penelitian ini yaitu data penjualan mobil listrik di Indonesia yang mempengaruhi tingkat polusi udara, kualitas udara serta mempengaruhi SDGs ke 7. Hasil penelitian menunjukkan adanya korelasi yang kuat antara peningkatan jumlah mobil listrik dan indeks kualitas udara serta penurunan tingkat polusi dan capaian SDGs ke 7. Pemerintah Indonesia masih memiliki tantangan seperti infrastruktur pengisian yang belum memadai dan harga jual yang tinggi. Strategi yang diusulkan meliputi peningkatan kebijakan regulasi, pembangunan infrastruktur pengisian daya yang ramah lingkungan, serta mendorong kerjasama dan investasi terutama dalam mendorong elemen dalam negeri.